2008
DOI: 10.1128/aac.01409-07
|View full text |Cite
|
Sign up to set email alerts
|

Production of Enterocins L50A, L50B, and IT, a New Enterocin, by Enterococcus faecium IT62, a Strain Isolated from Italian Ryegrass in Japan

Abstract: Enterococcus faecium IT62, isolated from ryegrass in Japan, was shown to produce three different bacteriocins, two of which had molecular masses and amino acid sequences that corresponded to those of enterocin L50A and enterocin L50B. These peptides existed, however, as chemically modified forms that were either N formylated or N formylated and oxidized at Met 24 . The third bacteriocin, named enterocin IT, had a molecular mass of 6,390 Da, was made up of 54 amino acids, and did not correspond to any known bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Some previous studies have reported about multiplebacteriocin-producing LAB such as Lactobacillus (Vaughan et al 2003), Enterococcus (Cintas et al 1998;Izquierdo et al 2008) and Leuconostoc (Papathanasopoulos et al …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported about multiplebacteriocin-producing LAB such as Lactobacillus (Vaughan et al 2003), Enterococcus (Cintas et al 1998;Izquierdo et al 2008) and Leuconostoc (Papathanasopoulos et al …”
Section: Discussionmentioning
confidence: 99%
“…Most LAB bacteriocins were synthesized as prepeptides containing N-terminal extension or leader sequences, while some class II bacteriocins have been reported to be synthesized without a leader sequence. The latter includes mutacin BHT-B (Hyink et al 2005), lacticin Q (Fujita et al 2007), lacticin Z (Iwatani et al 2007), enterocin Q (Cintas et al 2000) and enterocin L50 (Cintas et al 1998;Criado et al 2006a;Izquierdo et al 2008), most of which are class IId bacteriocins.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been reported that Met in bacteriocins become spontaneously oxidized, especially during their purification to homogeneity, leading to a loss or reduction of their antimicrobial activities (5,10,29). Moreover, a study carried out simultaneously with the one described herein reported the spontaneous chemical modification of EntL50A and EntL50B during their purification due to Met 1 formylation and Met 24 oxidation to MetSO, rendering active and inactive peptides, respectively (27). Considering that beer production includes a wort aeration step to promote brewing yeast growth and enhance the start-up of fermentation (47), the oxidative partial inactivation of EntL50A and EntL50B may hamper their application as beer biopreservatives at this stage of the brewing process.…”
Section: Discussionmentioning
confidence: 97%
“…The growth of indicator strains was monitored at 600 nm for 24 h at 37°C. Bacteriocin activity was expressed as the maximal difference in absorbance between controls and assays, which was reached at the end of the exponentialgrowth phase (between 7 and 10 h depending on the strain) (9).…”
Section: Methodsmentioning
confidence: 99%